2021
DOI: 10.1002/elsc.202100003
|View full text |Cite
|
Sign up to set email alerts
|

Interrogation of the perturbed gut microbiota in gouty arthritis patients through in silico metabolic modeling

Abstract: Recent studies have shown perturbed gut microbiota associated with gouty arthritis, a metabolic disease characterized by an imbalance between uric acid production and excretion. To mechanistically investigate altered microbiota metabolism associated with gout disease, 16S rRNA gene amplicon sequence data from stool samples of gout patients and healthy controls were computationally analyzed through bacterial community metabolic models. Patient‐specific community models constructed with the metagenomics modeling… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 74 publications
1
29
0
Order By: Relevance
“…In this study, we found that the genus Clostridium, Veillonella , and Streptococcus were more prevalent in HUA subjects than Con, consistent with a prior study in which Clostridium and Veillonella positively correlated with serum UA ( 31 ). The genus Clostridium is considered as an obese-associated genus in both Chinese ( 43 ) and Danish ( 44 ) populations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, we found that the genus Clostridium, Veillonella , and Streptococcus were more prevalent in HUA subjects than Con, consistent with a prior study in which Clostridium and Veillonella positively correlated with serum UA ( 31 ). The genus Clostridium is considered as an obese-associated genus in both Chinese ( 43 ) and Danish ( 44 ) populations.…”
Section: Discussionsupporting
confidence: 92%
“…Bacteroides possess an enrichment of the enzyme 5-hydroxysourate hydrolase, pivotal in gut uricolysis, and hence could regulate serum urate concentrations ( 30 ). On the other hand, elevated Bacteroides abundance may be a consequence of gout disease per se ( 31 ). Regardless, there are scant studies of asymptomatic individuals with HUA and their gut flora, which could provide prescient insight into the pathogenesis of the HUA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduced species abundance of Enterobacteriaceae was associated with amino acid metabolism and environmental perception, which together resulted in increased serum UA and C-reactive protein levels in gout patients ( Chu et al., 2021 ). After metagenomics and cluster analysis of feces from gout patients and healthy people, the samples were divided into high gout clusters dominated by Bacteroides and low gout clusters with increased Faecalibacterium ( Henson, 2021 ). The high gout cluster exhibited increased synthesis of the amino acids D-alanine and L-alanine and by-products of branched-chain amino acid catabolism, while the low gout cluster exhibited increased the production of butyrate, the sulfur-containing amino acids L-cysteine and L-methionine, and the L-cysteine catabolite H 2 S ( Henson, 2021 ).…”
Section: The Gut Microbiota In the Pathogenesis Of Hua And Goutmentioning
confidence: 99%
“…The gut microbiota is not only significantly related to diabetes but also its cause ( Vangipurapu et al., 2020 ; Zhang et al., 2021 ). The gut microbiota participates in purine and uric acid metabolism ( Henson, 2021 ). The kidneys excrete two-thirds of the human body’s uric acid, and the rest is mainly removed through the intestine ( Richette and Bardin, 2010 ).…”
Section: Introductionmentioning
confidence: 99%